Membingkai Ruang Dialog Beragama: Belajar dari Hans Kung dan Seyyed Hossein Nasr - Marz Wera (Reformed Center for Religion and Society, 2017)
ABSTRACT: Religious pluralism in Indonesia is currently in a state of confusion. The reality of religious diversity is insulated by misguided and superficial interpretations. The space for religious dialogue is entangled by group selfishness, squeezed by religious formalism, as well as claims of theological truth. The approach of dialogue, both exclusivism and inclusivism and even pluralism, has not been able to knit religious plurality. Traditions, symbols, rituals, ethical dimensions and the universal core in religions as a precondition of dialogue are actually a ignored. Such pluralism leads to the relativism of the teachings of religions. In that context, the author offers two approach concepts as a new way of interreligious dialogue. '' Global Ethics '' by Hans Kg and '' Perennial Philosophy '' by Seyyed Hossein Nasr. These two concepts provide an understanding of the unique and unique dimensions of religions that must be observed and should not be ignored. KEYWORDS: global ethics, Perennial Philosophy, traditions, dialogue, exclucivism, inclusivism, pluralism